A zero-carbon, reliable and affordable energy future in Australia. (1st April 2021) - Lu, Bin; Blakers, Andrew; Stocks, Matthew; Cheng, Cheng; Nadolny, Anna
Abstract: Australia has one of the highest per capita consumption of energy and emissions of greenhouse gases in the world. It is also the global leader in rapid per capita annual deployment of new solar and wind energy, which is causing the country's emissions to decline. Australia is located at low-moderate latitudes along with three quarters of the world's population. These factors make the Australian experience globally significant. In this study, a fully decarbonised electricity system is modelled together with complete electrification of heating, transport and industry in Australia leading to an 80% reduction in greenhouse gas emissions. An energy supply-demand balance is simulated based on long-term (10 years), high-resolution (half-hourly) meteorological and energy demand data. A significant feature of this model is that short-term off-river energy storage and distributed energy storage are utilised to support the large-scale integration of variable solar and wind energy. The results show that high levels of energy reliability and affordability can be effectively achieved through a synergy of flexible energy sources; interconnection of electricity grids over large areas; response from demand-side participation; and mass energy storage. This strategy could be a rapid and generic pathway towards zero-carbon energy futures within the Sunbelt. Highlights: Zero-carbon energy in Australia leads to an 80% reduction in the carbon emissions. Off-river pumped hydro energy storage and distributed energy storage for balancing. A high-voltage direct-current Super Grid spans much of the Australian continent. 100% renewable energy costs A$70-A$99 (US$49-US$69) per megawatt-hour in Australia. The Australian strategy is likely to be transferable to other Sunbelt countries.